LEARNING STRATEGIES ACROSS CULTURES OF EFL LEARNERS RESIDING IN EAST NUSA TENGGARA PROVINCE - Talok, Damianus; Erom, Kletus; Panis, Isabel Coryunitha (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
EFL learners employ a set of learning strategies in their learning of English. Learning strategies are claimed to be “internal mental drive” which EFL learners have in mind. Learning strategies are the internal power which enables EFL learners to acquire the so called language knowledge and language skills. It has been assumed that learning strategies are influenced by cultures of EFL learners. Consequently, EFL learners may employ different learning strategies, provided that EFL learners come from different cultures. This current research aims to disclose that each of EFL learners from the East Nusa Tenggara Province (NTT) employs learning strategies, as in fact that in NTT lives many cultures. Specifically, this research treated six EFL learners who are from different cultures. Two learners came from the inland area of Ende (Flores); other two students were from the inland area of Timor and two others were from the city of Kupang, the capital of Kupang Municipality. The results of the research show that these EFL learners use the same learning strategies entailing Metacognitive, cognitive and social mediation strategies. The outstanding discovery of this study is that EFL learners, in their learning, are very much influenced by the so called “instructional learning”. Learning does take place for there is  instruction from their teachers. Autonomous learning, as far as data are concerned, still does not take place. Thus culture, in this study, has no influence to EFL learners in terms of  the use of learning strategies among EFL learners with different cultural background.